2016
DOI: 10.1515/amm-2016-0248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron on Microstructure and Microhardness Properties of Mo-Si-B Based Coatings Produced Via TIG Process

Abstract: In this study, Mo-Si-B based coatings were produced using tungsten inert gas (TIG) process on the medium carbon steel because the physical, chemical, and mechanical properties of these alloys are particularly favourable for high-temperature structural applications. It is aimed to investigate of microstructure and microhardness properties of Mo-Si-B based coatings. Optical microscopy (OM), X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the microstructures of Mo-Si-B bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, these alloys show a lack of oxidation resistance in the intermediate temperature range, 650–750 °C, and possess a relatively high density (9.6 g/cm 3 ) compared to nickel‐based Superalloys . Islak et al quantified the molybdenum and boron content of Mo–Si–B based coatings, which are similar to the alloys used in this work, by energy dispersive X‐ray spectroscopy (EDS). The characterization of these alloys, especially the Mo 5 SiB 2 phase, with a scanning electron microscope (SEM) with X‐ray microanalysis analytical capabilities is a real challenge.…”
Section: Introductionmentioning
confidence: 97%
“…However, these alloys show a lack of oxidation resistance in the intermediate temperature range, 650–750 °C, and possess a relatively high density (9.6 g/cm 3 ) compared to nickel‐based Superalloys . Islak et al quantified the molybdenum and boron content of Mo–Si–B based coatings, which are similar to the alloys used in this work, by energy dispersive X‐ray spectroscopy (EDS). The characterization of these alloys, especially the Mo 5 SiB 2 phase, with a scanning electron microscope (SEM) with X‐ray microanalysis analytical capabilities is a real challenge.…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that Ti-Si-C-B containing coatings proffer integral excellent properties, produce unique ceramic phases of increased hardness values with several strengthening influence as a result of the enormous attraction among these elements [19][20][21]. The presence of Boron in coatings can refine the microstructure [22] and also increase the melting efficiency of hard SiC particles owing to the presence of a eutectic phase at 3.6 %B [11].…”
Section: 0introductionmentioning
confidence: 99%